ILMIY TADQIQOTCHILIK FAOLIYATINI AMALGA OSHIRISH MEXANIZMI - Otayeva, S.S. (SCIENCE and SOCIETY, 2023)
The article analyzes the content of scientific research activity and modern requirements for its component, as well as ways to achieve their effectiveness in the process of scientific activity.
Keywords: scientific research; science; reflex; reaction; hypothesis; competence approach; experience; pedagogical ability; creative ability